The Comparison of IC50 of Suji (Pleomele angustifolia) which is Extracted by Different Solvent - Bahri, Syamsul; Setiadi, Dadi; Lestari, Tri Ayu; Setiawan, Heru; Hakim, Muhammad Alfianul; Cahyadi, Lalu M. Zidan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The Determination both of IC50 of Suji (Pleomele angustifolia) and its phytochemical subtances content which extracted by a different solvent has been conducted. The aim of this research is to determine kind of solvent which achieve better result. The method used is laboratory experiments for phytochemical screening and antioxidant activity assay. This research consists of 2 (two) stages. First stage aims to obtain extract of suji by using certain solvent, and the second stage is carried out to examine secondary metabolite compounds of the extract using phytochemical screening and then to determine the antioxidant activity of extract using the DPPH method. This research used 2 kinds of solvent, ethanol plus ethyl acetate in the first sample, and the second one by ethanol only. Sample which extracted by ethanol plus ethyl acetate positively contains terpenoids, whereas flavonoid and alkaloids are detected in a significant number. The DPPH test results obtained the equation y = 0.3492x + 12,059, indicating that the antioxidant activity of suji which extracted by ethanol plus ethyl acetate is classified as moderate as the IC50 value of the extract of suji is108,65 ppm. The other sample which extracted just by ethanol also contains terpenoid, flavonoid, and alkaloid, but in a greater number. In the second sample also detected steroid compound which undetectable in the first sample. DPPH score in the second sample which extracted by ethanol. is y= 06352x + 18, 786. By using this equation we found 49.14 ppm as IC50 score. This score is classified as strong activity. This result shows that antioxidant activity of the second extract is stronger than the first one. The result also meaning that ethanol is more effective in extracting phytochemical compounds of suji than ethanol plus ethyl acetate.